2004
DOI: 10.1161/01.cir.0000135591.37759.af
|View full text |Cite
|
Sign up to set email alerts
|

Altered Titin Expression, Myocardial Stiffness, and Left Ventricular Function in Patients With Dilated Cardiomyopathy

Abstract: Background-The role of the giant protein titin in patients with heart failure is not well established. We investigated titin expression in patients with end-stage heart failure resulting from nonischemic dilated cardiomyopathy, in particular as it relates to left ventricular (LV) myocardial stiffness and LV function. Methods and Results-SDS-agarose gels revealed small N2B (stiff) and large N2BA (compliant) cardiac titin isoforms with a mean N2BA:N2B expression ratio that was significantly (PϽ0.003) increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
389
6
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 434 publications
(424 citation statements)
references
References 34 publications
27
389
6
2
Order By: Relevance
“…[28]. tio increases in muscles from patients with end-stage heart failure [85]. In this study, a positive correlation was found between the N2BA:N2B titin isoform ratio and various clinical parameters, such as the ratio of end-diastolic volume to end-diastolic pressure.…”
Section: Titin Isoform Switching In Chronic Heart Diseasesupporting
confidence: 55%
“…[28]. tio increases in muscles from patients with end-stage heart failure [85]. In this study, a positive correlation was found between the N2BA:N2B titin isoform ratio and various clinical parameters, such as the ratio of end-diastolic volume to end-diastolic pressure.…”
Section: Titin Isoform Switching In Chronic Heart Diseasesupporting
confidence: 55%
“…This probably reflects a compensatory effect of titin isoform expression. Consistent with previous studies [15,16], samples from failing hearts had a greater relative content of the large N2BA isoform of titin (p=0.047, Figure S3B). This isoform shift tends to decrease passive stiffness and seems to counteract the mechanical effect of increased fibrosis in the samples from the failing hearts.…”
Section: Failing Hearts Have Increased Mid-myocardial Fibrosissupporting
confidence: 90%
“…An increased proportion of the compliant N2BA variants was observed in end-stage failing human hearts, including those from ischemic cardiomyopathy, 105 nonischemic DCM, 109,110 and other patients with HFrEF, 111 compared with nonfailing donor hearts (45%-50% versus ≈30%). In patients with aortic stenosis, the N2BA:N2B expression ratio was somewhat higher than in healthy control hearts in one study, 111 but unaltered 112 or reduced 113 in other studies.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 99%
“…In contrast, characteristic for concentric remodeled hearts (compensated hypertrophy) with diastolic dysfunction following from hypertensive heart disease may be a decreased N2BA:N2B ratio causing elevated myocyte stiffness ( Figure 5A and 5B). Because the pattern of titin-isoform expression correlates with parameters of diastolic function, such as the end-diastolic volume, 110 it is likely that the titin-isoform ratio does affect overall myocardial passive stiffness. Not all relevant studies, however, have reported altered titin-isoforms in patients and HF models.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 99%